Effect of Graphene Concentration on the Electrochemical Properties of Cobalt Ferrite Nanocomposite Materials - Firas S. Alruwashid; Mushtaq A. Dar; Nabeel H. Alharthi; Hany S. Abdo (Nanomaterials, 2021)
A two-step process was applied to synthesize the cobalt ferrite-graphene composite materials in a one-pot hydrothermal reaction process. Graphene Oxide (GO) was synthesized by a modified Hummer’s method. The synthesized composite materials were characterized by X-ray diffraction (XRD), thermogravimetric analysis (TGA), field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), and Fourier-transform infrared spectroscopy (FTIR). The XRD and FTIR results were in good agreement with the TGA/DTG observations. SEM and TEM disclosed the spherical shape of the nanoparticles in 4–10 nm. The optimized CoFe2O4-G (1–5 wt.%) composite materials samples were tried for their conductivity, supercapacity, and corrosion properties. The CV results demonstrated a distinctive behavior of the supercapacitor, while the modified CoFe2O4-G (5 wt.%) electrode demonstrated a strong reduction in the Rct value (~94 Ω). The highest corrosion current density valves and corrosion rates were attained in the CoFe2O4-G (5 wt.%) composite materials as 5.53 and 0.20, respectively. The high conductivity of graphene that initiated the poor corrosion rate of the CoFe2O4-graphene composite materials could be accredited to the high conductivity and reactivity.